1979
DOI: 10.1007/bf00496051
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of three benzodiazepines in the social interaction anxiety test in mice

Abstract: The effects on active social interaction of acute and chronic dosage with diazepam (1 mg/kg), desmethyldiazepam (2 mg/kg), and chlor-desmethyl-diazepam (0.125 mg/kg) were studied in pairs of mice. The mice were tested under either high or low levels of illumination. In all cases acute drug treatment significantly reduced social interaction, but this was not seen with chronic treatment (9 days). Two of the drugs, diazepam and desmethyldiazepam, showed an anxiolytic action, i.e., these drugs resulted in signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(20 citation statements)
references
References 5 publications
2
18
0
Order By: Relevance
“…In experiments 2 and 4, under low lighting conditions there was no effect of familiarity. De Angelis and File (1979) noted in pilot experiments that the familiarity manipulation did not appear to work consistently in mice, and our more extensive investigations support this observation. In the present study the high lighting manipulation only decreased social interaction when mice were in the unfamiliar testing condition.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In experiments 2 and 4, under low lighting conditions there was no effect of familiarity. De Angelis and File (1979) noted in pilot experiments that the familiarity manipulation did not appear to work consistently in mice, and our more extensive investigations support this observation. In the present study the high lighting manipulation only decreased social interaction when mice were in the unfamiliar testing condition.…”
Section: Discussionsupporting
confidence: 69%
“…In the present study the high lighting manipulation only decreased social interaction when mice were in the unfamiliar testing condition. De Angelis and File (1979) found that increasing the light level decreased the social behavior of mice who were familiar with the test arena (but not with each other). Since our mice were also familiar with one another when tested in our "familiar condition", this might explain the discrepancy between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Chlordiazepoxide (CDZP) and other ben zodiazepine anxiolytics have been shown to be active in this model only after subacute (5 day) administration [2][3][4], Following studies of the factors influencing social behaviours, we have recently introduced a social interac tion (SI) protocol in which classically described aggres sive behaviours [5][6][7] are separated, and benzodiazepines are consistently detected after their acute administration [8,9). In this protocol a 'balanced conflict' [10] may exist between the desire to socially interact and the aversion caused by the presence of a novel partner.…”
Section: Introductionmentioning
confidence: 99%
“…The decline in social interaction induced by a novel environment or by high levels of illumination is prevented by anxiolytic drugs. Due to both the predominance of aggressive attacks in mice and their failure to respond to manipulations of the familiarity of the environment, this test does not seem to be applicable to this species (30,31). This procedure has frequently been used in developmental pharmacology and toxicology studies (23,32,33 …”
Section: Introductionmentioning
confidence: 99%